Local control of human papillomavirus infection after anal condylomata acuminata eradication - Manzione,Thiago da Silveira (2014)
OBJECTIVE: To verify whether the eradication of anal condylomata acuminata was effective for local control of HPV infection using anal colposcopy and anal brush cytology.METHODS: We evaluated 147 patients treated for anal margin and/or anal canal condyloma, with 108 HIV-positive and 39 HIV-negative individuals. The average age for males was 40 years for HIV-positive and 27.5 for HIV-negative. In females, the mean age was 37.5 years for HIV-positive and 31.5 for HIV-negative.RESULTS: Twenty-four patients (16.3%) had normal cytology and anal colposcopy, 16 (10.9%) normal cytology and altered anal colposcopy, 52 (35.4%) normal anal colposcopy and altered cytology, and 55 (37.4%) had altered cytology and anal colposcopy.CONCLUSION: the eradication of clinical lesions failed to locally control HPV infection.